Acute Cholecystitis: An Updated Review for Nursing Intervention Protocols - Alotaibi, Matar Awadh Gazi; Alotibi, Nourah Gassim Majari; Alfulayhani, Abdullah Saleh Ghuwainem; Alsharari, Maher Shaman Shutaywi; Alsharari, Rahi Shaman Shutaywi; Alsharari, Saleh Suwailem Muflih; Al-Hnedl, Abdullah Salem Hadi; Ahmed, Jumaan Said; Alanazi , Amal Hussain; Almasoudi, Tahani Saud; Jaberty , Wardah Yousef; Alotaibi, Khalid Shabab; et al. (Journal of Ecohumanism, 2024)
Background: Acute cholecystitis, an inflammation of the gallbladder, often presents with right upper quadrant pain, fever, and nausea. This condition can occur with or without gallstones, with acute cholecystitis being more severe. Differential diagnosis is crucial due to symptom overlapping with other conditions, such as peptic ulcer disease or pancreatitis. Effective diagnosis often combines clinical evaluation, imaging, and laboratory tests. Nurses play a significant role in addressing both the physical and emotional aspects of care. Aim: This review aims to provide an updated understanding of acute cholecystitis, focusing on nursing intervention protocols for effective patient care. Methods: The review was conducted by analyzing existing literature on cholecystitis pathophysiology, diagnosis, and nursing management. Key nursing diagnoses, including anxiety, pain, and nutritional deficits, were explored. Evidence from clinical guidelines and case studies was examined to identify the best practices for nursing interventions. Results: The review highlights several critical nursing interventions for acute cholecystitis management. These include pain management strategies, patient education to alleviate anxiety, monitoring nutritional status, and ensuring fluid balance. Early intervention and proper management, including preparation for surgery, significantly improve patient outcomes. Additionally, nursing roles in preoperative care, such as educating patients about the procedure and postoperative care expectations, are essential to reducing anxiety and promoting cooperation. Conclusion: Acute cholecystitis demands comprehensive nursing care, including pain relief, emotional support, and nutritional management. Nurses must be skilled in recognizing the symptoms, facilitating timely interventions, and preparing patients for surgery. Early diagnosis and individualized care plans are critical to improving recovery rates and reducing complications. Effective nursing management leads to improved patient comfort, reduced anxiety, and enhanced postoperative outcomes.